THE ROLE OF VILLAGE-OWNED ENTERPRISES IN EMPOWERING VILLAGE ECONOMIC POTENTIAL (CASE STUDY ON BATETANGNGA VILLAGE-OWNED ENTERPRISES AND BUMIAYU VILLAGE-OWNED ENTERPRISES IN POLEWALI MANDAR REGENCY) - Yamin, Muh Nur; Yusril, Muhammad; Sulmiah, Sulmiah (Universitas Negeri Makassar, 2024)
This study aims to determine the role of BUM Desa in empowering the economic potential of the village (case study in BUM Bumiayu Village and BUM Batetangnga Village in Polewali Mandar). This study uses a qualitative approach and produces descriptive data. Data collection was used by observation, interview, and documentation techniques. The data obtained from this study was then analyzed using data collection, data condensation, data presentation, and conclusion drawn.The results of this study show that the role of BUM Batetangnga Village in empowering the economic potential of the village is still not optimal. As for the implementation of four indicators, the role of BUM Desa in empowering the economic potential of the village, namely in regulators, dynamists, facilitators and catalysts. The constraints of the Batetangnga Village BUM include Human Resources (HR), science and technology, capital resources and cooperative relationships between communities. Meanwhile, BUM Bumiayu Village has shown success in empowering the economic potential of the village. And the factors of the success of BUM Bumiayu Village are Human Resources (HR), good community cooperation relationships, science, and capital resources.The conclusion in the implementation of the four indicators of the role of Village BUM in empowering the economic potential of the village from the two Village BUM is that the regulator indicator has not been successful, the dynamizer has been successful, the facilitator has succeeded and the catalyst is still not successful.